Constitutional reflections on academic freedom: the South African experience - Л. Пол; Р. Рена (Хабаршы. Психология және социология сериясы)
This study explores the intricate landscape of academic freedom within the constitutional framework of the Republic of South Africa (RSA). It emphasizes the interplay between academic freedom, institutional autonomy, and public accountability. The research examines various approaches to exercising academic freedom as a constitutional right, drawing on global best practices and assessing their relevance to South Africa's unique socio-political context. By analyzing judicial precedents, institutional practices, and societal dynamics, the study aims to offer nuanced insights into the evolving nature of academic freedom within the constitutional framework. The responsible exercise of academic freedom requires ethical considerations and respect for the rights of others. A balanced approach is essential to reconcile academic freedom with civic responsibility, ensuring that the quest for knowledge does not infringe upon individual dignity, privacy, or other fundamental rights. The study employs a diverse methodology, including a comprehensive legal analysis of constitutional provisions, a comparative assessment of international models, detailed case studies of South African Higher Education Institutions (HEIs), and interviews with stakeholders. This holistic approach, which integrates both qualitative and quantitative data, facilitates a more nuanced examination of academic freedom within the context. In essence, academic freedom is a pillar of South Africa's democratic culture, promoting intellectual inquiry, innovation, and societal progress. Its proper implementation, driven by ethical principles and institutional support, is critical to maintaining higher education's integrity and contributions to a just and equitable society.